Prioritization of the Skills to Be Mastered for the Daily Jobs of Japanese Dental Hygienists - Yoshiaki Nomura; Erika Kakuta; Ayako Okada; Yuko Yamamoto; Hiroshi Tomonari; Noriyasu Hosoya; Nobuhiro Hanada; Naomi Yoshida; Noriko Takei (International Journal of Dentistry)
Dental hygienists require proficiency in a wide variety of job skills. Dental hygienists should master their job skills step by step, and the prioritization of these steps is important. In this study, we investigated the frequency at which Japanese dental hygienists performed daily jobs and attempted to classify the jobs according to the proficiency levels. The aim of this study was to surmise the order in which skills should be mastered in terms of priority and to investigate the relationship between daily jobs and the motivation for completing jobs. The Japan Dental Hygienists’ Association conducts a survey on the employment status of dental hygienists in Japan every five years. The questionnaire is distributed to all members of the Japan Dental Hygienists’ Association. In this study, the responses of 3,807 dental hygienists who worked at dental clinics were analyzed. We analyzed 77 kinds of daily jobs and the items regarding the motivation to work. For the analysis, item response theory (IRT), structural equation modeling (SEM), and logistic regression analysis were applied. According to the item response curve, the jobs were classified into 11 clusters. The jobs classified into Cluster 1 were the jobs that most of the average-proficiency Japanese dental hygienists performed. Scaling and root planing were the representative jobs in Cluster 1. Performing the jobs classified into Cluster 5 clearly discriminated whether the dental hygienists were performing multiple jobs. Jobs concerning care for elderly or disabled patients were classified into Cluster 5. Jobs concerning gerodontology, implants, management of staff, and consultations were significantly associated with the motivation to perform jobs. Polishing and adjustment of orthodontic apparatuses was negatively associated with the motivation to perform jobs. Understanding the features of each daily job of dental hygienists is important for planning dental hygienists’ lifelong educational programs and evaluating their skill levels and proficiency levels. The results presented in this study may help to reveal the characteristics of dental hygienists’ daily jobs.